Novel PD-1-targeted, activity-optimized IL-15 mutein SOT201 acting in cis provides antitumor activity superior to PD1-IL2v - Ulrich Moebius; Radek Špíšek; David Béchard; Zuzana Antosova; Nada Podzimkova; Irena Adkins; Klara Danova; Ekaterina Simonova; Katerina Behalova; Petr Danek; Matej Fabisik; Kamila Hladikova; et al. (Journal for ImmunoTherapy of Cancer)
Background SOT201 and its murine surrogate mSOT201 are novel cis-acting immunocytokines consisting of a humanized/murinized/, Fc-silenced anti-programmed cell death protein 1 (PD-1) monoclonal antibody (mAb) fused to an attenuated human interleukin (IL)-15 and the IL-15Rα sushi+ domain. Murine mPD1-IL2v is a conjugate of a murinized, Fc silenced anti-PD-1 mAb bearing human IL-2 with abolished IL-2Rα binding. These immunocytokines spatiotemporally reinvigorate PD-1+ CD8+ tumor-infiltrating lymphocytes (TILs) via cis-activation and concomitantly activate the innate immunity via IL-2/15Rβγ signaling.Methods Human peripheral blood mononuclear cell and cell lines were used to evaluate cis/trans activity of SOT201. Anti-PD-1 mAb responsive (MC38, CT26) and resistant (B16F10, CT26 STK11 KO) mouse tumor models were used to determine the anticancer efficacy, and the underlying immune cell activity was analyzed via single-cell RNA sequencing and flow cytometry. The expansion of tumor antigen-specific CD8+ T cells by mSOT201 or mPD1-IL2v and memory CD8+ T-cell generation in vivo was determined by flow cytometry.Results SOT201 delivers attenuated IL-15 to PD-1+ T cells via cis-presentation, reinvigorates exhausted human T cells and induces higher interferon-γ production than pembrolizumab in vitro. mSOT201 administered as a single dose exhibits strong antitumor efficacy with several complete responses in all tested mouse tumor models. While mPD1-IL2v activates CD8+ T cells with a 50-fold higher potency than mSOT201 in vitro, mSOT201 more effectively reactivates effector exhausted CD8+ T cells (Tex), which demonstrate higher cytotoxicity, lower exhaustion and lower immune checkpoint transcriptional signatures in comparison to mPD1-IL2v in MC38 tumors in vivo. This can be correlated with a higher rate of complete responses in the MC38 tumor model following mSOT201 treatment when compared with mPD1-IL2v. mSOT201 increased the relative number of tumor antigen-specific CD8+ T cells, and unlike mPD1-IL2v stimulated greater expansion of adoptively transferred ovalbumin-primed CD8+ T cells simultaneously limiting the peripheral CD8+ T-cell sink, leading to the development of memory CD8+ T cells in vivo.Conclusions SOT201 represents a promising therapeutic candidate that preferentially targets PD-1+ TILs, delivering balanced cytokine activity for reviving CD8+ Tex cells in tumors. SOT201 is currently being evaluated in the Phase I clinical study VICTORIA-01 (NCT06163391) in patients with advanced metastatic cancer.